A critical review of the commercial vaibility of interest-free banking in Singapore - Goh, Siew Yee (2008)
With the worldwide growing interest in interest-free banking (also known as Islamic banking), we seek to explore the viability of such a system in Singapore. From the experiences of other Islamic countries and those conventional institutions which have tapped into the vast potential of this innovative banking alternative, we anticipate that it may enhance Singapore's competitiveness in her bid to become the regional financial centre. Our research focuses on whether Singapore has sufficient demand for interest-free banking. Quantitative analysis has been conducted to determine the amounts of deposits required for interest-free units for institutions to be commercially viable.